Business Plan for Recy-Qlo - Li, Yuanpeng; Kussainova, Assel (2016)
Recy-Qlo is a new venture that is aiming to implement two business ideas: Therma-Qlo (TQ) and Ethi-Qlo (EQ). EQ collects post consumer textiles discarded by residents/enterprises for reselling second-hand clothing/upcycled items. Whereas TQ produces thermal insulation materials from post consumer textiles collected by EQ and greasy wool. TQ is the main business, meanwhile EQ is a supplementary business model targeted mostly at collecting and promoting the value of textile re-use through creating/selling innovative products from discarded textiles.